Investigation and functional characterization of rare genetic variants in the adipose triglyceride lipase in a large healthy working population. - Stefan Coassin; Martina Schweiger; Anita Kloss-Brandstätter; Claudia Lamina; Margot Haun; Gertraud Erhart; Bernhard Paulweber; Yusof Rahman; Simon Olpin; Heimo Wolinski; Irina Cornaciu; Rudolf Zechner; et al. (PLoS Genetics)
Recent studies demonstrated a strong influence of rare genetic variants on several lipid-related traits. However, their impact on free fatty acid (FFA) plasma concentrations, as well as the role of rare variants in a general population, has not yet been thoroughly addressed. The adipose triglyceride lipase (ATGL) is encoded by the PNPLA2 gene and catalyzes the rate-limiting step of lipolysis. It represents a prominent candidate gene affecting FFA concentrations. We therefore screened the full genomic region of ATGL for mutations in 1,473 randomly selected individuals from the SAPHIR (Salzburg Atherosclerosis Prevention program in subjects at High Individual Risk) Study using a combined Ecotilling and sequencing approach and functionally investigated all detected protein variants by in-vitro studies. We observed 55 novel mostly rare genetic variants in this general population sample. Biochemical evaluation of all non-synonymous variants demonstrated the presence of several mutated but mostly still functional ATGL alleles with largely varying residual lipolytic activity. About one-quarter (3 out of 13) of the investigated variants presented a marked decrease or total loss of catalytic function. Genetic association studies using both continuous and dichotomous approaches showed a shift towards lower plasma FFA concentrations for rare variant carriers and an accumulation of variants in the lower 10%-quantile of the FFA distribution. However, the generally rather small effects suggest either only a secondary role of rare ATGL variants on the FFA levels in the SAPHIR population or a recessive action of ATGL variants. In contrast to these rather small effects, we describe here also the first patient with "neutral lipid storage disease with myopathy" (NLSDM) with a point mutation in the catalytic dyad, but otherwise intact protein.